Nilai Didaktis dalam Kumpulan Dongeng Jejak-Jejak Misterius - Priyono Priyono; Junita Yosephine Sinurat; Nicky Rosadi (Neolectura, 2021)
The purpose of this study was to determine the didactic value contained in a collection of fairy tales. The method used in this research is descriptive qualitative with content analysis techniques. The object of this research is the eight fairy tales contained in Jejak-Jejak Misterius tale collection. The findings from the results of this study are the didactic values contained in Jejak-Jejak Misterius tale collection, namely the values of initiative, discipline, criticality, diligence, social, attitude, and divine.